Meat intake and cancer risk: prospective analyses in UK Biobank - Knuppel, A; Papier, K; Fensom, G; Appleby, P; Schmidt, JA; Tong, Y; Wrightson, R; Key, T; Perez-Cornago, A (Oxford University Press, 2020)
Background Red and processed meat have been consistently associated with colorectal cancer risk, but evidence for other cancer sites and for poultry intake is limited. We therefore examined associations between total, red and processed meat and poultry intake and incidence for 20 common cancers.